Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.18632/oncotarget.15681
|View full text |Cite
|
Sign up to set email alerts
|

The histone demethylaseKDM3Aregulates the transcriptional program of the androgen receptor in prostate cancer cells

Abstract: The lysine demethylase 3A (KDM3A, JMJD1A or JHDM2A) controls transcriptional networks in a variety of biological processes such as spermatogenesis, metabolism, stem cell activity, and tumor progression. We matched transcriptomic and ChIP-Seq profiles to decipher a genome-wide regulatory network of epigenetic control by KDM3A in prostate cancer cells. ChIP-Seq experiments monitoring histone 3 lysine 9 (H3K9) methylation marks show global histone demethylation effects of KDM3A. Combined assessment of histone dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
86
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(89 citation statements)
references
References 77 publications
1
86
0
Order By: Relevance
“…Moreover, the DEGs were found to be elevated in clinical metastatic PCa [47]. The expression of AR or its target genes were unaffected by shKDM3B treatment, thus demonstrating that KDM3B, in contrast to other KDM members, does not act via AR [11,18,37,62]. LNCaP cells were largely unaffected by KDM3B knockdown.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Moreover, the DEGs were found to be elevated in clinical metastatic PCa [47]. The expression of AR or its target genes were unaffected by shKDM3B treatment, thus demonstrating that KDM3B, in contrast to other KDM members, does not act via AR [11,18,37,62]. LNCaP cells were largely unaffected by KDM3B knockdown.…”
Section: Discussionmentioning
confidence: 96%
“…3a). Isoform-1 (1761 AA) is proposed to be the canonical form with a Jumonji-C (JmjC) domain, C2HC4 zinc-finger domain, serine-rich domain, and a LxxLL motif [36,37]. Isoform-2 is slightly shorter with a truncated N-terminus [38], while Isoform-3 lacks the first 1000 amino acids and does not contain the nuclear localization signal [38].…”
Section: Loss Of Kdm3b Causes Decreased Androgenindependent Growth Anmentioning
confidence: 99%
“…Methylation of histone lysine is important for epigeneticassociated gene expression profiles in cancer. 6,7 Histone methylation profiles have been demonstrated to be critical in developmental biology, neurological disorders, and numerous cancer types. [8][9][10] In addition, hypoxia modulates histone-modifying factor expression, leading to changes in histone marks.…”
mentioning
confidence: 99%
“…Therefore, understanding how KDM3A specifically regulates gene expression is an area of current inquiry and is vital for understanding epigenetics in human disease. KDM3A activity is deregulated in several cancers, including prostate, 7,18 breast, 19 and Ewing sarcoma. 20,21 KDM3A regulates several transcription factors, such as PPARG, KLF2, ESR1, and HOXA1.…”
mentioning
confidence: 99%
“…As well as modulating gene expression, this modification is involved in X-chromosome inactivation [3,4], DNA damage repair [5], and in the determination and differentiation of embryonic stem cells [6,7]. However, it is widely reported that dysregulation of HMT expression and activity is frequently observed in cancer [8][9][10][11]. Two main histone residues, arginine and lysine groups, are methylated by HMTs.…”
Section: Introductionmentioning
confidence: 99%